Targeting T Cell Metabolism in Inflammatory Skin Disease - von Meyenn, Leonhard; Bertschi, Nicole Leonie; Schlapbach, Christoph (Frontiers in Immunology, 2019)
A properly functioning T cell compartment is crucial to protect the host from infections, tumors and environmental substances. In recent years, it has become increasingly clear that the processes underlying proper T cell activation, proliferation, and differentiation require well-tuned and dynamic changes in T cell metabolism. Thus, proper metabolic reprogramming in T cells is crucial to ensure proper immunity in the context of infection and anti-tumor immunity. Conversely, aberrant regulation of T cell metabolism can impair T cell function and thereby contribute to T cell-mediated disease. In this review, the relevance of recent insights into T cell metabolism for prototypical T cell-mediated skin diseases will be discussed and their therapeutic potential will be outlined. First, the major modules of T cell metabolism are summarized. Then, the importance of T cell metabolism for T cell-mediated skin diseases such as psoriasis and allergic contact dermatitis is discussed, based on the current state of our understanding thereof. Finally, novel therapeutic opportunities for inflammatory skin disease that might emerge from investigations in T cell metabolism are outlined.